'We Want What the Ok Tedi Women Have!' Guidance from Papua New Guinea on Women's Engagement in Mining Deals - Menzies, Nicholas; Harley, Georgia (World Bank, Washington, DC, 2014)
Despite global gender equality gains in education, life expectancy, and labor force participation, two areas of persistent inequality remain: asset gaps and women's agency. In many developing countries, including Papua New Guinea (PNG), land and natural resources are citizens' key assets. This briefing note, centered on field research in north fly district explores the process of negotiation and the progress in implementation of the Community Mine Continuation Agreements (CMCAs). The purpose of the research and the resulting brief is to understand how the CMCAs came about, assess whether their promise is being realized in practice, and provide guidance for mining and gender practitioners looking to use mining agreements to improve development outcomes for women, both in PNG and further afield. Revised compensation agreements at the Ok Tedi mine, called CMCAs, concluded in 2007 are an encouraging innovation. In these revised CMCAs, women had a seat at the negotiating table and secured an agreement giving them 10 percent of all compensation, 50 percent of all scholarships, cash payments into family bank accounts (to which many women are cosignatories), and mandated seats on the governing bodies implementing the agreement (including future reviews of the agreement). The 2006-07 Ok Tedi negotiation process and the resulting CMCAs were internationally groundbreaking for having secured enhanced rights for women in legally enforceable mining agreements, even in a context of severe gender inequality. Nevertheless, the gender asset gaps that persist in the midst of the current global extractives boom highlight the need to engage women more proactively in mining agreements and support their ability to exercise greater agency over those resources. More attention to the principles and experiences of community-driven development, together with more local political economy analysis, will likely benefit women's engagement and outcomes.